Breakthrough events in the biography of the family system – developmental and educational significance - Kuryś-Szyncel, Karolina (Difficult situation in biographies: Volume 9, 2025)
Starting from the analogy between Kazimierz Obuchowski’s concept of the authorial man and Niklas Luhmann’s understanding of the system and the category of autopoiesis that connects them, the author points to a possible new reading of the educational and developmental potentials of the family system in the face of citical events which can become a contribution to biographical learning in the sense of Peter Alheit. She refers to the category of family biography, by which she understands a multiplied (being more than the sum of individual biographies), subject to the systemic principles of circularity and equipotentiality, infinite reconstruction resulting from the tension between the course of the family’s life and the story of the history of life. The adopted perspective allows us to look at family biography as the effect of the struggle of individual members of the family system and the whole family with breakthrough events of both a normative (inscribed in the course of life) and non-normative nature (e.g. critical life events). The author indicates the effects of coping with these events, distinguishing developmental effects as (re)constructions of the family system and educational effects as (re) constructions of the family biography.